SYNTHETIC BIOLOGY-DRIVEN BIOPLASTICS: A LIFE CYCLE ASSESSMENT AND ENVIRONMENTAL IMPACT STUDY - Ardi Azhar Azhar; Livia Alves; Raul Gomez (Research of Scientia Naturalis, 2025)
The pervasive environmental pollution caused by petroleum-based plastics has catalyzed the search for sustainable alternatives. Bioplastics, derived from renewable biomass, offer a promising solution, yet their production can be inefficient and compete with food resources. Synthetic biology provides powerful tools to engineer microorganisms for the high-yield production of bioplastics like polyhydroxyalkanoates (PHA) from non-food feedstocks. This study aimed to conduct a comprehensive life cycle assessment (LCA) to quantify and compare the environmental impacts of PHA produced via a synthetically engineered microbial platform against conventional polyethylene terephthalate (PET). A "cradle-to-grave" LCA methodology was employed, encompassing feedstock cultivation, fermentation, polymer extraction, and end-of-life scenarios including landfilling and industrial composting. The results revealed that the synthetic biology-driven PHA exhibited a 65% lower global warming potential and a 70% reduction in non-renewable energy use compared to PET. However, it showed higher impacts in eutrophication and land use, linked to its lignocellulosic feedstock origins. The end-of-life analysis confirmed the significant advantage of PHA’s biodegradability. This study concludes that while synthetic biology-driven bioplastics offer substantial benefits in carbon footprint and fossil fuel dependency, a holistic view is crucial.